The Effectiveness of a proposed program in fractal geometry in development the spatial ability and teaching Performance for mathematics teachers of upper PrimaryStage in Nablus - Wala’ Jehad Dahman (My University, 2015)
This study aimed to find out the effectiveness of a proposed program in fractal geometry in development the spatial ability and teaching performance for mathematics teachers of upper primary stage in Nablus. The researcher tried specifically to answer this question: What is the effectiveness of a proposed program in fractal geometry in development the spatial ability and teaching performance for mathematics teachers of upper primary stage in Nablus? To answer the study question and its hypotheses, the researcher applied a Quasi Experimental approach and the Qualitative approach on a sample of mathematics teachers of upper primary stage during the first semester 2014-2015. The sample was divided into two groups; one is Experimental, the other is Control.The Experimental group has been trained using fractal geometry, while the compared group has been trained in the traditional way. -The Vandenberg Mental was used to measure spatial ability for teachers after training on the program of fractal geometry. The validity and the reliability of the test were calculated, and the value of reliability was (0.71). - Identification of teaching performance, to measure teaching performance after training on the program of fractal geometry. The validity and the reliability were calculated, and the value of reliability was (0.95). To test the hypothesis, the data were analyzed by using One-Way Analysis of Variance ANCOVA, and by using Pearson correlation to examine the relation between spatial ability and the teaching performance. The results of the study were: 1- There is a significant statistical difference at (α=0.05) between the mean of spatial ability for teachers who were trained on the program of fractal geometry and the mean of teachers who training on the traditional way. The results were in favor of the treatment group. 2- There is a significant statistical difference at (α=0.05) between the mean of the teaching performance for teachers who training on the program of fractal geometry and the mean for teachers who training on the traditional way. The results were in favor of the treatment group. 3- There is a significant statistical difference at (α=0.05) between the teachers on spatial ability test, and teaching performance. It is a positive relation. When the spatial ability is increased, the teaching performance of teachers will be increased also. On the basis of the results, the researcher recommended to tegration fractal geometry as a subject in the book of the methods of teaching mathematics to students teachers, also recommends to include the fractal geometry in the mathematics curricula of different educational stages, and to attachment mathematics with arts and nature.

هدفت هذه الدراسة إلى معرفة فاعلية برنامج تدريبي في هندسة الفراكتال في تنمية القدرة المكانية وتحسين الأداء التدريسي لدى معلمي الرياضيات للمرحلة الأساسية العليا في محافظة نابلس، وتحديداً الإجابة عن السؤال الرئيس الآتي: ما فاعلية برنامج مقترح في هندسة الفراكتال في تنمية القدرة المكانية وتحسين الأداء التدريسي لدى معلمي الرياضيات للمرحلة الأساسية العليا في محافظة نابلس؟ وللإجابة عن سؤال الدراسة واختبار فرضياتها، استخدمت الباحثة تصميماً شبه تجريبي، وطُبقت الدراسة على عينة من معلمي الرياضيات للمرحلة الأساسية العليا، وتمّ تقسيمهم إلى مجموعتين؛ إحداهما تجريبية تم تدريبها باستخدام هندسة الفراكتال، والأخرى ضابطة تم تدريبها بالطريقة الإعتيادية، وذلك في الفصل الأول من العام (2014-2015) وقد طُبقت على عينة الدراسة الأدوات الآتية: 1. اختبار فاندنبرغ لقياس القدرة المكانية ((The Vandenberg Mental Rotation Test، لقياس القدرة المكانية بعد التدريب على البرنامج المقترح في هندسة الفراكتال، وقد تم التحقق من صدقه بعرضه على محكمين، وتم حساب معامل ثباته، فكانت قيمته (.710). 2. استبانة الأداء التدريسي، لقياس الأداء التدريسي بعد التدريب على البرنامج المقترح في هندسة الفراكتال، وقد تم التحقق من صدقه بعرضه على محكمين، وتم حساب معامل ثباته، فكانت قيمته (0.95). وقد عولجت البيانات باستخدام تحليل التباين الأُحادي المصاحب؛ لفحص دلالة الفرق في متوسطي القدرة المكانية والأداء التدريسي للمجموعتين الضابطة والتجريبية، وباستخدام معامل ارتباط بيرسون (Pearson correlation coefficient) لفحص العلاقة بين القدرة المكانية والأداء التدريسي، وقد توصلت الدراسة إلى النتائج التالية: 1. وجود فرق ذي دلالة إحصائية عند مستوى الدلالة (0.05 =α) بين متوسطي القدرة المكانية لمعلمي المجموعة التجريبية، والمجموعة الضابطة على الدرجة الكلية لاختبار القدرة المكانية البعدي يُعزى إلى طريقة التدريب (الإعتيادية، استخدام البرنامج المقترح في هندسة الفراكتال). وذلك لصالح المجموعة التجريبية التي تدربت باستخدام البرنامج المقترح في هندسة الفراكتال 2. وجود فرق ذي دلالة إحصائية عند مستوى الدلالة (0.05=α) بين متوسطي الأداء التدريسي لمعلمي المجموعة التجريبية والمجموعة الضابطة على مقياس الأداء التدريسي تُعزى إلى طريقة التدريب (الإعتيادية، استخدام البرنامج المقترح في هندسة الفراكتال). وذلك لصالح المجموعة التجريبية التي تدربت باستخدام البرنامج المقترح في هندسة الفراكتال. 3. وجود علاقة ارتباطية ذات دلالة إحصائية عند مستوى الدلالة (0.05=α) بين القدرة المكانية، والأداء التدريسي لمعلمي الرياضيات للمرحلة الأساسية العليا، وهي علاقة إيجابية أي بزيادة القدرة المكانية لدى المعلمين يزداد مستوى أدائهم التدريسي. وفي ضوء هذه النتائج أوصت الباحثة بعدد من التوصيات، ومن أهمها دمج هندسة الفراكتال كموضوع دراسي إثرائي في مقرر لطرق تدريس الرياضيات للطلاب المعلمين بكلية التربية، كما وتوصي بتضمين هندسة الفراكتال في مناهج الرياضيات بالمراحل التعليمية المختلفة وبمستويات مناسبة، وربط الرياضيات بالفنون والطبيعة وذلك من خلال عمل مشروعات طلابية تستند على أُسس هندسة الفراكتال.
فاعلية برنامج مقترح في هندسة الفراكتال في تنمية القدرة المكانية والأداء التدريسي لدى معلمي الرياضيات للمرحلة الأساسية العليا في محافظة نابلس